Three-dimensional architecture hybrid perovskite solar cells using CdS nanorod arrays as an electron transport layer. (11th December 2017) - Song, Zihang; Tong, Guoqing; Li, Huan; Li, Guopeng; Ma, Shuai; Yu, Shimeng; Liu, Qian; Jiang, Yang
Abstract: Three-dimensional (3D) architecture perovskite solar cells (PSCs) using CdS nanorod (NR) arrays as an electron transport layer were designed and prepared layer-by-layer via a physical-chemical vapor deposition (P-CVD) process. The CdS NRs not only provided a scaffold to the perovskite film, but also increased the interfacial contact between the perovskite film and electron transport layer. As an optimized result, a high power conversion efficiency of 12.46% with a short-circuit current density of 19.88 mA cm −2, an open-circuit voltage of 1.01 V and a fill factor of 62.06% was obtained after 12 h growth of CdS NRs. It was four times the efficiency of contrast planar structure with a similar thickness. The P-CVD method assisted in achieving flat and voidless CH3 NH3 PbI3− x Cl x perovskite film and binding the CdS NRs and perovskite film together. The different density of CdS NRs had obvious effects on light transmittance of 350–550 nm, the interfacial area and the difficulty of combining layers. Moreover, the efficient 1D transport paths for electrons and multiple absorption of light, which are generated in 3D architecture, were beneficial to realize a decent power conversion efficiency.